2011
DOI: 10.1186/1471-2121-12-32
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-mimetic agents inhibit proliferation and alter the morphology of human umbilical cord-derived mesenchymal stem cells

Abstract: BackgroundThe therapeutic efficacy of human mesenchymal stem cells (hMSCs) for the treatment of hypoxic-ischemic diseases is closely related to level of hypoxia in the damaged tissues. To elucidate the potential therapeutic applications and limitations of hMSCs derived from human umbilical cords, the effects of hypoxia on the morphology and proliferation of hMSCs were analyzed.ResultsAfter treatment with DFO and CoCl2, hMSCs were elongated, and adjacent cells were no longer in close contact. In addition, vacuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 37 publications
(39 reference statements)
7
31
0
Order By: Relevance
“…3). Several studies have also reported the Co ion-induced suppression of cellular growth and the significant dose-dependent toxicity behaviors (1 to 100 µM Co ions) [16,29]. While suppressing a certain level of cellular viability, the Co has also been shown to significantly improve the angiogenesis, including VEGF production through the hypoxicinduced HIF-1α pathway [29].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…3). Several studies have also reported the Co ion-induced suppression of cellular growth and the significant dose-dependent toxicity behaviors (1 to 100 µM Co ions) [16,29]. While suppressing a certain level of cellular viability, the Co has also been shown to significantly improve the angiogenesis, including VEGF production through the hypoxicinduced HIF-1α pathway [29].…”
Section: Discussionmentioning
confidence: 96%
“…In fact, studies have used Co ions (CoCl 2 ) to simulate hypoxic cell culture conditions, where the common concentration used was 100 µM [15,16,28]. Taking the release amount of Co ions into consideration from our results (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…MSCs exposed to hypoxic conditions exhibit greater colony-forming potential and proliferate faster and longer. Exposure of MSCs to hypoxia also prolonged their differentiation [10]. The mechanism of the therapeutic benefits of HPC must be multifaceted, at least enhanced expression and release of trophic and growth factors that provide autocrine and paracrine effects of protection and motivation of regenerative responses [11].…”
Section: Introductionmentioning
confidence: 99%
“…In view of the fact that DFO belongs to a class of hypoxia mimetic agents which also inhibit cell proliferation 21 , Song et al 6 chose another iron chelator mimosine (MIM) structurally different from DFO.…”
Section: C-kitmentioning
confidence: 99%